Cellular and molecular immune response and production performance of Indian white shrimp Penaeus indicus (H. Milne-Edwards, 1837), reared in a biofloc-based system with different protein levels of feed. Issue 119 (December 2021) - Panigrahi, A.; Das, R.R.; Sundaram, M.; Sivakumar, M.R.; Jannathulla, R.; Lalramchhani, C.; Antony, Jose; Shyne Anand, P.S.; Vinay Kumar, K.; Jayanthi, M.; Dayal, J.S.
Abstract: The present study focuses on the immunity and growth of Penaeus indicus fed with varying protein levels (25%, 30%, and 35%) in a biofloc based rearing system. A 120 days growth trial was carried out using juvenile Penaeus indicus (0.71 ± 0.01) with dietary protein level, 25% (LP), 30% (MP), and 35% (HP), and a control diet-fed with 35% acted as control group resulting in 4 treatments each with four replicates and were randomly assigned 16 tank units (7500 L each). A combination of different carbon sources (molasses, wheat flour, and rice bran in 2:1:1 ratio), yeast and a probiotic ( Bacillus sp.) consortium were used for the development of biofloc. At the end of the trial, the growth parameters of shrimps viz ., initial weight, feed conversion ratio (FCR), and daily growth coefficient (DGC) were computed. The results indicated that shrimp fed with medium (30%) protein (MP) diet recorded significantly (P < 0.05) improved growth performance compared to high protein fed group (35%) and low protein (25%) fed group (LP) in a biofloc system and control group (35%). The immunological parameters such as hemagglutination activity (HA) assay, serum protein, lysozyme, phenol oxidase (PO), and inhibition of superoxide dismutase (SOD) activity were observed in serum, plasma, and hemocyte lysate supernatant (HLS). The HA activity, PO activity in plasma was found to be higher in high protein fed animals, whereas medium protein resulted in enhanced PO activity in serum. Similarly, lysozyme and SOD were inhibited well in high protein fed animals compared to the low protein fed group. The vital immune genes's mRNA profiling showed a potential rise in the expressional pattern in MP and HP treatments compared to LP and control. BGBP (beta-1, 3-glucan binding protein) and hemocyanin mRNA transcript levels were highly upregulated in the HP (5 fold) and moderately expressed in MP (2 fold) and LP (1–2 fold). The transcripts of peroxinectin, antimicrobial peptides like crustin showed significant upregulation in HP followed by in MP and LP and control. Likewise, other immune genes, such as SOD, prophenoloxidase (proPO), showed a similar trend in a marginal way, indicating immunomodulation in the biofloc groups. This study suggested that biofloc with high protein (35%) supplementation can substantially enhance the immune response of shrimps, although medium protein level (30%) is optimum for improving the survival, growth, and in turn economic return in Indian white shrimp. Highlights: Indian white shrimp Penaeus indicus is suitable candidate species under Biofloc based farming (BFT) system. Improved production performances of this shrimp were observed in the BFT system irrespective of the differential protein level in feed. Comparative upregulation in gene expression according to the increased protein level were evident. Bio-floc system improves growth performance, immune response in this shrimp in low protein fed system on par with high protein fed groups.